Rancang Bangun dan Uji Kinerja Alat Pemisah Kernel Sawit dari Cangkangnya dengan Menggunakan Larutan Garam - Hidayatullah, Martin Sulung; Tamrin, Tamrin; Oktafri, Oktafri; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2023)
.  Palm oil has an important role to play in improving the country's foreign exchange.  The largest selling point in palm oil is palm kernel oil (PKO), this palm kernel oil processing process involves a mixture of kernels and shells that will later be separated.  This research aims to design the build and produce a prototype kernel separator from its shell by using a saline solution to minimize excess costs and able to separate the kernel and shell >80%.  Methods carried out in this study include designing, manufacturing and testing.  After that, prototype kernel separator with palm shell using salt solution with tool dimensions on container length 53 cm, width 40 cm, height 42 cm, water receiver body length 22 cm, width 16 cm, height 28.  The kernel separator with palm shell using this saline solution is able to separate the kernel and shell mixture by 82%. Keywords: Design, Kernel,Palm Oil, Shell, Separation.